Abnormal thermal stability of sub-10 nm Au nanoparticles and their high catalytic activity. Issue 18 (23rd January 2019) - Cao, Xiaoqing; Zhou, Jun; Wang, Hongna; Li, Song; Wang, Wei; Qin, Gaowu
Abstract : Abnormal thermal stability and high catalytic activity of sub-10 nm Au nanoparticles prepared by novel interfacial plasma electrolytic oxidation. Abstract : Supported Au nanoparticles have been attracting increasing attention due to their unique catalytic performance. However, their thermal and catalytic stability against sintering and aggregation during preparation and reactions remains a serious issue in practical applications, and what is even more difficult is to solve this mutually exclusive problem by a feasible technique. Here, we propose a simple one-step ultra-low temperature interfacial plasma electrolytic oxidation (ULTPEO) process to successfully prepare sub-10 nm and highly stable Au NPs, supported on a porous MgO layer, with high activity and a long lifespan. The obtained Au NPs, with partially exposed free surfaces, are encapsulated into a porous MgO support film. This unique embedded structure restrains their sintering on the support surface during high temperature treatment even up to 600 °C and shows good thermal stability and excellent recyclability in a model reaction of the hydrogenation of 4-nitrophenol. Moreover, the developed technique allows the facile control of the average size of Au NPs down to ∼3 nm with high monodispersity by liquid nitrogen cooling, and hence a further significant improvement in catalytic activity and the lowest catalytic activation energy of ∼14 kJ mol −1 among the reported literature are obtained. This simple technique is also extended to other metal NP catalysts ( e.g. Ru and Pd) that support MgO and exhibit excellent catalytic activity for the hydrolysis of sodium borohydride and oxidation of silanes, respectively.